Agrarian Reforms and Democracy in Africa: Changes or Continuity? The Case-Studies of Zimbabwe and South Africa (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The consolidation of democracy in Africa has been characterized by different events with different and usually controversial outcomes, especially in its relationship with the safeguard of land rights. The article aims to discuss these elements starting from the controversial historical relationship between democracy and agricultural reform (in its different acceptations, including property title registration forms), a topic of fundamental importance, albeit slightly under-investigated today, for the redefinition of the relationship with citizens and the strengthening of democracy and development. Following from a discussion of the general questions, the paper will focus on Southern Africa, where the topic has historically been a hot one and now involves unresolved transitions, as shown in the case studies of Zimbabwe and South Africa.
Keywords: Agrarian Reform; Land Control; Rural Development; Zimbabwe; South Africa.